Citrus BMP Implementation in Florida's Gulf Citrus Production Area: Pesticides: AE511/AE511, 2/2015 - Watson, Jonathan A.; Wysocki, Allen F.; Bucklin, Ray A. (EDIS, 2015)
This paper explores the transformative role of technology in supply-chain management within the food industry, focusing on electronic devices, information technology, and green and sustainable technologies. We explore how electronic devices and information technology have revolutionized inventory tracking, quality monitoring, and supply chain coordination, resulting in enhanced efficiency and reduced waste. The paper also discusses emerging technologies like blockchain, artificial intelligence, and machine learning, highlighting their potential to revolutionize traceability, quality control, and personalized consumer experiences. Additionally, green, and sustainable technologies are explored, focusing on their role in transportation, packaging, and production practices. While acknowledging the benefits, the paper also discusses the limitations and challenges associated with these technologies, including cost considerations, interoperability issues, and environmental impacts.